2010
DOI: 10.1097/brs.0b013e3181d12627
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Deformity Correction and Clinical Outcomes After Thoracoscopic Scoliosis Surgery

Abstract: Patients undergoing thoracoscopic anterior scoliosis correction reported good SRS scores which are comparable with those in previous studies. Postoperative major Cobb angle is a significant predictor of patient satisfaction when comparing subgroups of patients with the highest and lowest postoperative Cobb angles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Multiple discectomies and compression along the rod lead to shortening of the anterior column and immediate increases in the thoracic kyphosis at the first erect radiograph after surgery, with further increases reported two years after anterior selective thoracic fusion [5,7,8,14,16,18]. Prior studies by our group on the larger cohort have reported complications associated with this type of surgery [8,41,58]. In the current cohort of 30 patients, there were 3 rod fractures and 3 top screw pullouts found by the most recent follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…Multiple discectomies and compression along the rod lead to shortening of the anterior column and immediate increases in the thoracic kyphosis at the first erect radiograph after surgery, with further increases reported two years after anterior selective thoracic fusion [5,7,8,14,16,18]. Prior studies by our group on the larger cohort have reported complications associated with this type of surgery [8,41,58]. In the current cohort of 30 patients, there were 3 rod fractures and 3 top screw pullouts found by the most recent follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…Does it really matter if the curve was reduced to 35° 25° or 15°? Several studies have shown that if the Cobb angle is reduced to 35° or less the SRS-22 outcome score will be the same for curves corrected to 35° or 25° or 15° [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Izatt et al [30] prospectively reviewed 100 patients undergoing thoracoscopic scoliosis surgery for AIS. The patients reported good post-operative patient reported outcome scores [30]. Newton et al [31] reported similar good patient satisfaction scores in 41 patients undergoing anterior thoracoscopic scoliosis surgery for thoracic scoliosis.…”
Section: Surgical Treatmentmentioning
confidence: 99%